Nuclear Factor I-C Regulates Stemness Genes and Proliferation of Stem Cells in Various Mineralized Tissue through Epithelial-Mesenchymal Interactions in Dental Epithelial Stem Cells - Dong-Seol Lee; Yeo Joon Song; Hye Ri Gug; Ji-Hyun Lee; Hyun Sook Bae; Joo-Cheol Park (Hindawi Limited, 2022)
Tooth development includes numerous cell divisions and cell-cell interactions generating the stem cell niche. After an indefinite number of divisions, pluripotent cells differentiate into various types of cells. Nuclear factor I (NFI) transcription factors are known as crucial regulators in various organ development and stem cell biology. Among its members, nuclear factor I-C (NFI-C) has been reported to play an essential role in odontogenesis. Nfic knockout mice show malformation in all mineralized tissues, but it remains unclear which stage of development Nfic is involved in. We previously reported that Nfic induces the differentiation of ameloblast, odontoblast, and osteoblast. However, the question remains whether Nfic participates in the late stage of development, perpetuating the proliferation of stem cells. This study aimed to elucidate the underlying mechanism of NFI-C function in stem cells capable of forming hard tissues. Here, we demonstrate that Nfic regulates Sox2 and cell proliferation in diverse mineralized tissue stem cells such as dental epithelial stem cells (DESCs), dental pulp stem cells, and bone marrow stem cells, but not in fibroblasts. It was also involved in the expression of pluripotency genes Lin28 and NANOG. Especially in DESCs, Nfic regulates the proliferation of epithelial cells via epithelial-mesenchymal interactions, which are the Fgf8-Nfic-Sox2 pathway in epithelium and Nfic-Fgf10 in the mesenchyme. Moreover, Nfic slightly increased reprogramming efficiency in induced pluripotent stem cells of mineralized tissues, but not in soft tissues. In conclusion, these results suggest that Nfic is a crucial factor for maintaining the stem cell niche of mineralized tissues and provides a possibility for Nfic as an additional factor in improving reprogramming efficiency.